A GDP-mannose-1-phosphate guanylyltransferase as a potential HIGS target against Sclerotinia sclerotiorum. - Cheng Zhang; Yan Xu; Lin Li; Mingsong Wu; Zheyi Fang; Jinyi Tan; Jeffrey A Rollins; Honghui Lin; Xinyi Huang; Shawn D Mansfield; Xin Li; Yuelin Zhang (PLoS Pathogens)
Sclerotinia stem rot is a devastating disease affecting vegetables and oil crops worldwide. It is caused by the necrotrophic ascomycete Sclerotinia (S.) sclerotiorum. Host-induced gene silencing (HIGS) has shown promise in disease control against insects and fungal pathogens, but effective HIGS target genes against S. sclerotiorum remain limited. In this study, we identified a GDP-mannose pyrophosphorylase (GMPP) SsMPG2 through forward genetic analysis. Ssmpg2 mutants exhibit abnormal sclerotia and compound appressoria, along with defective cell wall integrity and attenuated virulence. Meanwhile, knocking out SsMPG2 reduced the GMPP activity and glycosylation of proteins. In addition, SsMPG2 interacts with SsMPG1, which is essential in S. sclerotiorum. Downstream of the SsMPG1-SsMPG2 complex, SsPMT4, which encodes an O-mannosyltransferase, is also critical for compound appressoria formation and virulence. Notably, MPG2 is essential for the virulence of several other fungal pathogens such as Botrytis cinerea, Magnaporthe oryzae, and Fusarium graminearum. Furthermore, expressing hairpin RNAs against SsMPG1 and SsMPG2 in Nicotiana benthamiana and Arabidopsis thaliana significantly reduced disease symptoms caused by S. sclerotiorum. Collectively, our findings demonstrate the critical roles of GMPP in the virulence of phytopathogenic fungi and suggest that MPGs are promising HlGS targets for controlling S. sclerotiorum.